2018
DOI: 10.1002/jcp.27282
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‐143‐5p is required for the promotion of odontoblasts differentiation of human dental pulp stem cells through the activation of the mitogen‐activated protein kinases 14‐dependent p38 mitogen‐activated protein kinases signaling pathway

Abstract: MicroRNAs (miRNAs) play critical roles in various biological processes including cell differentiation. Some researchers suggested that the p38 mitogen-activated protein kinases (MAPK) signaling pathway had an effect on regulating the odontoblastic differentiation of human dental pulp stem cells (hDPSCs). This study focuses on the effects of miR-143-5p on hDPSCs by regulating the p38 MAPK signaling pathway. The targeting relationship of MAPK14 and miR-143-5p targets were verified by TargetScan and dual-lucifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…It has been reported that miR-143-5p binds to MAPK14 and reduces its expression. Thus, miR-143-5p knockdown increases MAPK14 expression and activates the p38 MAPK signaling pathway, consequently enhancing the odontogenic differentiation [ 151 ]. In addition, by directly targeting tumor necrosis factor- α (TNF- α ), miR-143 blockades the NF- κ B signaling pathway and suppresses the osteogenic differentiation [ 152 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…It has been reported that miR-143-5p binds to MAPK14 and reduces its expression. Thus, miR-143-5p knockdown increases MAPK14 expression and activates the p38 MAPK signaling pathway, consequently enhancing the odontogenic differentiation [ 151 ]. In addition, by directly targeting tumor necrosis factor- α (TNF- α ), miR-143 blockades the NF- κ B signaling pathway and suppresses the osteogenic differentiation [ 152 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…This suggests that miR-143-5p could be developed as a target of genetically modified stem cell therapy for pulp regeneration. Another study of Wang et al [55] also identified the inhibitory role of miR-143-5p in the odontogenic differentiation of human DPSCs. They showed that the downregulated miR-143-5p expression induced the expression of the p38 MAPK signaling pathway-related gene MAPK14 and odontogenesis-related markers.…”
Section: Anti-odontogenic Differentiation Mirnasmentioning
confidence: 89%
“…In the research on ncRNAs and their roles in the odontogenic differentiation of hDPSCs, the most studied are miRNAs. miR-223-3p and miR-21 have been shown to promote odontogenic differentiation, while miR-143-5p, miR-140-5p, and miR-488 inhibit this process [41][42][43][44][45][46]. In 2016, Chen et al found that lncRNA differentiation antagonizing non-protein coding RNA (DANCR) inhibited the odontogenic differentiation of human dental pulp cells by inactivating the Wnt/β-catenin signaling pathway [16].…”
Section: Discussionmentioning
confidence: 99%